Developing a Performance Management System for World-class Project Execution - Lezala, Benjamin Peter (2011)
Bombardier Transportation UK Ltd (BTUK) is a division of Bombardier Transportation – the global leader in rail technology offering the broadest product portfolio in the rail industry including passenger rail vehicles and total transit systems. BTUK is a project-based company which from 2005 has been required to deliver 11 different and very complex rail vehicle projects. Resources have been stretched and the robustness of internal business processes has been tested. Company performance has suffered with many projects running late and failing to meet financial targets. This poor performance can be attributed in the first instance to a lack of organisation leadership, poor application of the performance management process, and lack of discipline in the governance process. More fundamentally, the poor performance is due to the current performance management system focussing on retrospective financial indicators, resulting in a lack of focus on day-to-day leading operational performance measures. The BTUK experience demonstrates that if the operational performance is not good, the financial and schedule performance will also be poor.